Pengaruh Digital Marketing, Customer Review, dan Flash Sale Terhadap Keputusan Pembelian Konsumen Di Apikasi Shopee (Studi Mahasiswa Pengguna Aplikasi Shopee Universitas Islam Malang) - Safrillia, Dea; Arifin, Rois; Saraswati, Ety (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This study aims to analyse and describe the effect of digital marketing, customer reviews, and flash sales on consumer purchasing decisions in the Shopee application (study on students of the Islamic University of Malang). The population in this study were students of the Islamic University of Malang. Which obtained a sample of 95 people using the Malhotra formula. The variables used in this study are purchasing decision variables (dependent variables), while the independent variables are digital marketing, customer reviews, and flash sales.The results of this study concluded that there was a positive and significant influence between digital marketing, customer review, and flash sale variables on purchasing decisions and simultaneously concluded that there was an influence between digital marketing, customer review, and flash sale on purchasing decisions. Keywords: Purchasing Decisions, Digital Marketing, Customer Reviews, and Flash Sales.